KHARMA: An open KML/HTML architecture for mobile augmented reality applications - Hill, A; MacIntyre, B; Gandy, M; Davidson, B; Rouzati, H (2010 9th IEEE International Symposium on Mixed and Augmented Reality, 2010)
Widespread future adoption of augmented reality technology will rely on a broadly accessible standard for authoring and distributing content with, at a minimum, the flexibility and interactivity provided by current web authoring technologies. We introduce KHARMA, an open architecture based on KML for geospatial and relative referencing combined with HTML, JavaScript and CSS technologies for content development and delivery. This architecture uses lightweight representations that decouple infrastructure and tracking sources from authoring and content delivery. Our main contribution is a re-conceptualization of KML that turns HTML content formerly confined to balloons into first-class elements in the scene. We introduce the KARML extension that gives authors increase control over the presentation of HTML content and its spatial relationship to other content.